Pengaruh Bauran Promosi Terhadap Keputusan Pembelian Tiket Event Badminton Influencer Tournament Pada Ideal Foundation Medan - Gilang Perkasa, Christianto Brian; Manurung, John Sihar (Civiliza Publishing, 2025)
The promotional mix includes advertising, sales promotion, personal selling, public relations and direct marketing plays an important role in shaping consumer perception and interest in an event. All of these elements contribute synergistically in influencing consumers' decisions to buy event tickets. This research aims to determine the influence of the promotional mix on the decision to purchase tickets for the Badminton Influencer Tournament event at the Ideal Foundation Medan. This research uses quantitative methods with a simple linear regression test. Data was collected by distributing questionnaires to all respondents. The sampling technique uses probability sampling with the Slovin formula. The independent variables used are advertising, sales promotion, personal selling, public relations and direct marketing. The data analysis technique uses multiple linear analysis. The data analysis methods in this research are data quality testing, classical assumption testing, multiple linear analysis and hypothesis testing using SPSS version 26. The results of this research are that partially sales promotion, public relations and marketing directly influence purchasing decisions, while advertising and sales personality does not influence the decision to visit. Simultaneously advertising, sales promotion, direct sales, public relations and direct marketing influence the decision to visit. Overall promotional mix variables consisting of advertising, sales promotion, personal sales, public relations and marketing directly influence the decision to purchase tickets for the Badminton Influencer Tournament event by 56.7% while the remaining 43.3% can be explained by other factors not examined in this research.